The black hole transient MAXI J1348–630: evolution of the compact and transient jets during its 2019/2020 outburst. Issue 1 (26th March 2021) - Carotenuto, F; Corbel, S; Tremou, E; Russell, T D; Tzioumis, A; Fender, R P; Woudt, P A; Motta, S E; Miller-Jones, J C A; Chauhan, J; Tetarenko, A J; Sivakoff, G R; et al.
ABSTRACT: We present the radio and X-ray monitoring campaign of the 2019/2020 outburst of MAXI J1348–630, a new black hole X-ray binary (BH XRB) discovered in 2019 January. We observed MAXI J1348–630 for ∼14 months in the radio band with MeerKAT and the Australia Telescope Compact Array, and in the X-rays with MAXI and Swift /XRT. Throughout the outburst, we detected and tracked the evolution of compact and transient jets. Following the main outburst, the system underwent at least four hard-state-only re-flares, during which compact jets were again detected. For the major outburst, we observed the rise, quenching and reactivation of compact jets, as well as two single-sided discrete ejecta travelling away from the BH, launched ∼2 months apart. These ejecta displayed the highest proper motion (≳100 mas d −1 ) ever measured for an accreting BH binary. From the jet motion, we constrain the ejecta inclination and speed to be ≤46 ○ and ≥0.69 c, and the opening angle and transverse expansion speed of the first component to be ≤6 ○ and ≤0.05 c . We also infer that the first ejection happened at the hard-to-soft state transition, before a strong radio flare, while the second ejection was launched during a short excursion from the soft to the intermediate state. After travelling with constant speed, the first component underwent a strong deceleration, which was covered with unprecedented detail and suggested that MAXI J1348–630 could be located inside a low-density cavity in the interstellar medium, as already proposed for XTE J1550–564 and H1743–322.